Democracy, state capacity and the governance of COVID-19 in Asia-Oceania - Croissant, Aurel; Hellmann, Olli (Routledge, Taylor & Franics Group, 2023)
"This book examines the public health responses to the COVID-19 pandemic in the Asia-Oceania region and their implications for democratic backsliding. The contributions discuss three key questions: How did political institutions in Asia-Oceania create incentives for effective public health responses to the COVID-19 outbreak? How did state capacities enhance governments' ability to implement public health responses? How have governance responses affected the democratic quality of political institutions and processes? Together, the analyses reveal the extent to which institutions prompted an effective public health response and highlights that a high-capacity state was not a necessary condition for containing the spread of COVID-19 during the early phase of the pandemic. By combining quantitative and qualitative analyses the volume also shows that the effect of the COVID pandemic on the quality of democratic institutions has been uneven across Asia-Oceania. Guided by a comprehensive theoretical framework this will be an invaluable resource for scholars and students of political science, policy studies, public health and Asian studies"--